The Influence of Globalization in Indonesia’s National Legal Order - Christwan, Christwan; Ginting, Salmon (Jurnal Indonesia Sosial Sains, 2025)
Globalization is not something that can be avoided by a country and will make significant changes in various sectors that can have potential and negative impacts. The changes that will and will definitely occur are in the legal order of a country, in this case Indonesia, although there is an adage that says "the law always limps with the times" but the legal impact that occurs due to globalization must be addressed wisely so that the law due to change can still be applied according to the values of Pancasila and the 1945 Constitution. What must be done is to harmonize national law and international law due to the influence of globalization so that it is appropriate according to the adage that says that "law will always provide a remedy or solution".